2023
DOI: 10.3390/metabo13050598
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Secondary Metabolites in Fruits and Leaves of Cloudberry (Rubus chamaemorus L.)

Abstract: Cloudberry (Rubus chamaemorus L.) is a circumpolar boreal plant rich in bioactive compounds and is widely used in food and in folk medicine. In this study, a combination of two-dimensional NMR spectroscopy and liquid chromatography–high-resolution mass spectrometry was used for the comprehensive characterization of secondary metabolites in cloudberry lipophilic and hydrophilic extracts. Special attention was paid to the leaf extractives, which are highly enriched in polyphenolic compounds, the content of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The average range of the total phenolic content in the R. idaeus fruits determined with the Folin-Ciocalteau method in the present study (1.0 mg/g in 'Glen Ample'-1.3 mg/g in 'Radziejowa') was in agreement with the range reported for the raspberry cultivars 'Aksu Kırmızısı' (1.0-1.8 mg/g), 'Rubin' (1.1-1.9 mg/g), 'Heritage' (1.3-1.9 mg/g), and 'Autumn Bliss' (1.1-2.5 mg/g), but lower than the values reported for R. idaeus 'Newburgh' (1.4-1.8 mg/g), Heritage (1.5-1.9 mg/g), 'Hollanda Boduru (1.8-2.1 mg/g) [62], 'Fallgold' (1.5-1.5 mg/g), 'Meeker' (2.1 mg/g) [63], and cloudberry R. chamaemorus L. (7.0 mg/g) [64]. These differences are mainly related to environmental factors.…”
Section: Polyphenolic Compounds and Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The average range of the total phenolic content in the R. idaeus fruits determined with the Folin-Ciocalteau method in the present study (1.0 mg/g in 'Glen Ample'-1.3 mg/g in 'Radziejowa') was in agreement with the range reported for the raspberry cultivars 'Aksu Kırmızısı' (1.0-1.8 mg/g), 'Rubin' (1.1-1.9 mg/g), 'Heritage' (1.3-1.9 mg/g), and 'Autumn Bliss' (1.1-2.5 mg/g), but lower than the values reported for R. idaeus 'Newburgh' (1.4-1.8 mg/g), Heritage (1.5-1.9 mg/g), 'Hollanda Boduru (1.8-2.1 mg/g) [62], 'Fallgold' (1.5-1.5 mg/g), 'Meeker' (2.1 mg/g) [63], and cloudberry R. chamaemorus L. (7.0 mg/g) [64]. These differences are mainly related to environmental factors.…”
Section: Polyphenolic Compounds and Antioxidant Activitymentioning
confidence: 99%
“…Since the total phenolic content in the studied raspberry cultivars is comparable to the antioxidant activity determined by the DPPH and ABTS assays, it may be supposed that the antioxidant activity of fruits is mainly related to the presence of polyphenols. Faleva et al [64] have reported that the antioxidant activity of raspberry fruit extracts depends on the high content of ascorbic acid.…”
Section: Polyphenolic Compounds and Antioxidant Activitymentioning
confidence: 99%
“…The authors performed a targeted metabolomic analysis using LC-MS/MS on syrup and powder matrices to optimise various factors to isolate and identify the largest number of metabolites per analysis. Also, recent attempts at comprehensive isolation and characterisation of secondary metabolites include the report by Faleva et al [18] in Rubus chamaemorus lipophilic and hydrophilic extracts using a combination of 2D nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography-high-resolution mass spectrometry (LC-HRMS). They reported on a total of 68 compounds from their analyses.…”
Section: Warburgia Salutaris Extraction Solvent Phytochemical Analysi...mentioning
confidence: 99%